Establishment of BALB/C mouse models of influenza A H1N1 aerosol inhalation. Issue 11 (30th July 2019) - Hao, Xin‐Yan; Li, Feng‐Di; Lv, Qi; Xu, Yan‐Feng; Han, Yun‐Lin; Gao, Hong
Abstract: Influenza A (H1N1) is a rapidly spreading acute respiratory illness that remains a worldwide burden on public health. To simulate natural infection routes, BALB/C mice were challenged with the H1N1 virus by aerosol and intranasal instillation routes. We compared the weight change and survival of the mice for 14 consecutive days after infection. The infected mice were euthanized at days 3, 5, 7, and 9 to perform necropsies, lung pathological analyses, viral titers measurement, and lung cytokines examination. The aerosol‐treated mice showed clinical symptoms on day 4, obvious lung lesions on day 5, rapid weight loss on day 7, peak virus replication in the lungs on days 7 to 9, and bronchial epithelial hyperplasia on day 9. However, after intranasal instillation, the mice exhibited clinical signs on day 2, rapid weight loss and obvious lung lesions on day 3, and peak virus replication in the lungs on days 3 to 5; no bronchial epithelial hyperplasia was detected. High levels of proinflammatory cytokines and chemokines were detected in the lungs of infected mice by both two routes. Disease and lung lesion progressions were slower in the mice that inhaled H1N1‐containing aerosols than in those treated by intranasal instillation, and lung lesions were homogeneous in the aerosol group and heterogeneous in the intranasal group. In this study, BALB/C mouse models of H1N1 virus aerosol inhalation were successfully established and compared with mouse models of intranasal inoculation, aerosol mouse models had an infection route and lung pathology characteristics that more closely resembled those observed in humans. Highlight: To simulate the natural route, BALB/C mice were infected successfully with H1N1 aerosol. And mice without anesthesia were exposed simultaneously to H1N1 aerosol by an animal nose‐only exposure device. Compared with intranasal mouse models, aerosol mouse models more closely resemble human infection in terms of the infection route and pathological changes in the lungs.